Analyzing the Role of Educational Games in Project-Based Learning to Enhance Students' Problem-Solving Skills - Gunawan Gunawan; Kosim Kosim; Ahmad Harjono; Muh. Makhrus (Indonesian, 2024)
This study investigates the role of game-based educational tools within a Project-Based Learning (PBL) framework in enhancing students' problem-solving skills. Faced with the demands of Industry 4.0 and the Sustainable Development Goals (SDGs), there is a critical need for innovative learning approaches that foster problem-solving and creativity among prospective teachers. This research adopted a 4D model (Define, Design, Develop, Disseminate) to develop a game-based PBL learning device, tested over six months with 27 university students across different semesters. The findings indicate that the integration of educational games significantly contributes to the development of problem-solving abilities. Students actively engaged in real-world project challenges through games, which facilitated the identification, formulation, strategy implementation, and solution verification stages of problem-solving. While the 'identifying problems' and 'verifying solutions' aspects showed areas for further improvement, the overall process demonstrated a positive impact on students' capacity to tackle complex issues effectively. This highlights the potential of game-based PBL as an engaging and effective pedagogical tool for cultivating essential problem-solving competencies in higher education.